The alternation of neural oscillations during dual task standing in older adults with low back pain - Le Ge; Yao Zu; Zhicheng Li; Xin Li; Huanjie Huang; Yan Li; Xiaoyu Gao; Xi Chen; Qiuhua Yu; Chuhuai Wang (European Review of Aging and Physical Activity)
Abstract Background Previous studies showed that the difficulty levels of posture and cognitive tasks and pain could interactively modulate the brain oscillations. Older adults with low back pain (LBP) have poorer postural control than healthy older adults under dual-task conditions. However, the underlying mechanism remains unclear. Hence, this study aimed to investigate alterations in brain activation during dual tasks in older people with LBP. Methods This cross-sectional study involved older participants with LBP (n = 21) and healthy older adults (n = 18) without a history of LBP. Electroencephalogram data and balance performance data were recorded simultaneously during dual and single tasks that required the participants to maintain stability in posture tasks with or without a concurrent cognitive task. The posture tasks had two levels of difficulty: a two-leg stance and one-leg stance. Cognitive tasks involved three levels of difficulty: no-cognition tasks, counting tasks, and arithmetic tasks. Brain activities were assessed using the power spectral density (PSD) of alpha-, beta-, and theta-band power rhythms within three regions of interest including the frontal, central, and parietal regions of the brain. Results A repeated-measures analysis of variance (2 postural tasks × 3 cognitive tasks × 2 groups) was used to test balance performance, cognitive performance and brain activities under different task conditions between the two groups. Compare to controls, LBP participants showed poorer performance in postural tasks (reflected by larger COP parameters) and cognitive tasks (reflected by lower accuracy rates) regardless of task difficulty level (p < 0.05). LBP participants showed larger COP parameters in the dual task with high and low cognitive difficulties than those in single task (p < 0.05), which was not observed in control group. The theta band power of control group was higher during one-leg stance than during two-leg stance in frontocentral regions (p < 0.05), which was not observed in LBP group. The LBP group showed greater beta-band power in the frontal regions than the control group in all conditions(p < 0.05). Correlations between COP parameters and theta band power in frontal regions were significant in dual task or one-leg stance(p < 0.05). Conclusions In older people with LBP, the brain oscillations as assessed on the PSD of beta and theta power rhythms is changed under the dual-task condition compared with control group. Cognitive and postural difficulty levels could modulate theta band power in frontal region, which subsequently affected the balance performance in older people with LBP.